Understanding Client Approval Time Through Customer Journey Analysis in VR and Non-VR Interior Design Workflows - Satria Putra Pamungkas (Journal of Consumer Studies and Applied Marketing, 2025)
Interior design results from repeated interactions between clients and designers, which often lead to approval delays that disrupt workflow, and reduce project efficiency. This study examines how such delays occur during the schematic design stage at Visial Studio by using Customer Journey Analysis (CJA) to compare VR and non-VR presentation methods. The study aims at establishing the causes of long client approval time which may result in delays in the timelines, inefficiencies and decreased client satisfaction. This study introduces a novel application of CJA within the interior design context, especially in the schematic design phase. Although VR is widely discussed in design practice, no empirical work has examined how visualization tools shape the actual sequence of client-designer interactions. By reconstructing customer journeys through methodological triangulation of communication records, approval documents, and revision files, the analysis compares planned workflow expectations with the actual journey to reveal deviations and their causes. The findings provide empirical insights into individual customer journeys and identify two additional types of delays, timing and iteration, extending the four deviation types originally defined by Halvorsrud et al. (2016).The analysis shows that delays are due to timing issues, while iteration reflects refinement rather than failure in interior design service delivery. VR presentations improved client understanding and decision clarity, eliminating failing touchpoints across all VR cases. Nevertheless, VR did not necessarily reduce the general schematic timeline. The speed of approval was still greatly dependent on external factors, such as the type of client, type of project, project size and readiness of the site. Overall, this study demonstrates how CJA can reveal the mechanisms behind approval delays in interior design services and highlights the conditions under which VR can enhance, but not necessarily accelerate, schematic design workflows.